The cultural practice from the decentralized autonomous government of Canton Pindal - Escudero Sánchez, Carlos Leonel; Pacheco Montoya, Emma Patricia (Journal of business and entrepreneurial studie, 2023)
The Decentralized Autonomous Government of the canton Pidal, performs social practices where a cultural dimension is expressed, in which infinite artistic expressions and manifestations of local, regional and national identity are linked, these actions place cultural practices in an identity with respect to ideology, not as false consciousness, This practice can be carried out following the traditional ways in which it is done from the municipal activity where it has served interests linked to the maintenance of social oppression, or it can deploy coherent ways with social emancipation in which people and human groups become protagonists giving solution to their problems. The research work created a project with a community self-development approach to strengthen the cultural management of the Directorate of Social Development of the Municipality of Pindal, it began with an initial participatory diagnosis on cultural practices, to propose a cultural agenda to improve the management of the social and cultural area of the local government of the canton of Pindal through the methodology of community self-development.